Improvement of Buckwheat Malt Technology - Koshova, Valentina; Kobernitska, Alina; Kinash, Dasha (My University, 2017)
This work was dedicated to the study of the effect of malting temperature on the chemical composition of buckwheat malt. It was found that steeping and malting buckwheat set the optimum mode soaking 4 extracts of buckwheat under water and 6 hours of air pauses steeping water temperature 16ºS within 24-32 hours.Malting also held at different temperatures: 14, 16 and 18ºC. The optimum temperature was 16ºS duration germination 24 - 32 hours. At this temperature, malting and humidity 44% maximum capacity amylolytic malt was after the first day and was 320ed.
Keywords: гречка; солод; солодорощення; вологість; температура; амілолітична активність; buckwheat; malt; germination; moisture content; temperature; amylolytic ability; кафедра біотехнології продуктів бродіння і виноробства